ANALYSIS OF THE CURRENT STATE OF TAXATION OF INDIVIDUAL ENTREPRENEURS AND SELF-EMPLOYED PERSONS IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2024)
The article covers the analysis of the work carried out in streamlining, supporting and granting benefits to individual entrepreneurs and self-employed persons in order to ensure the employment of the population and to attract them widely to entrepreneurial activities, reforms carried out to increase the scale of functioning and newly established individual entrepreneurs and self-employed persons.